2010
DOI: 10.5152/jtgga.2010.06
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of diabetes mellitus at postpartum six to twelve months following the diagnosis of gestational diabetes mellitus

Abstract: Objective:The aim of this study was to research the rates of diabetes mellitus (DM) and the risk factors that may play a role in the prediction of this condition by evaluating patients with the diagnosis of gestational diabetes mellitus (GDM) at the 6 th -12 th postpartum months. Material and Method:Among 109 cases who had been invited to the hospital for oral glucose tolerance test (OGTT) at the 6 th -12 th postpartum months, 84 cases (77%) were enrolled in the study. To the 78 patients that were found to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Another report by Langer showed that fasting glucose > 105 mg/dL was associated with fetal macrosomia, hypoglycemia in newborn infants, cesarean delivery, and a need for insulin therapy [48]. Previous studies have failed to determine an association between fasting glucose and future progression to type 2 diabetes for several reasons as follows: it was not measured [49]; the variable was not entered in the statistical model [50]; or modeling excluded GDM women with high fasting glucose level [39, 51] in the studies [7, 52]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another report by Langer showed that fasting glucose > 105 mg/dL was associated with fetal macrosomia, hypoglycemia in newborn infants, cesarean delivery, and a need for insulin therapy [48]. Previous studies have failed to determine an association between fasting glucose and future progression to type 2 diabetes for several reasons as follows: it was not measured [49]; the variable was not entered in the statistical model [50]; or modeling excluded GDM women with high fasting glucose level [39, 51] in the studies [7, 52]. …”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies have shown an association of maternal age, parity, and a family history of diabetes with glucose intolerance, but reports are inconsistent [7, 39, 52]. …”
Section: Discussionmentioning
confidence: 99%
“…In our study, one-fifth of the women who participated in the screening in the postpartum phase was diagnosed with type 2 diabetes by the physician. In a similar study, 78 women had an OGTT between the 6th and 12th months postpartum, and according to the screening results, 34.6% of women were found to have type 2 diabetes and 35.9% were found to have impaired glucose tolerance or impaired fasting glucose [4]. In other studies, the prevalence of type 2 diabetes was reported between 4.5% and 30%, according to the results of postpartum screening among women who were diagnosed with GDM during pregnancy [7,15,[18][19][20][21].…”
Section: University Hospital In Turkeymentioning
confidence: 93%
“…There is a risk of developing type 2 diabetes from GDM during and after the postpartum period. In the literature, it has been reported that approximately one-third of women diagnosed with GDM develop type 2 diabetes in the postpartum period [4], and more than half University hospital in Turkey of them who are diagnosed with GDM develop type 2 diabetes in five years [3]. Women with a history of GDM may prevent or delay the risk of developing type 2 diabetes through healthy lifestyle changes, such as a healthy diet, reaching an ideal weight and maintaining it, engaging in regular physical activity and quitting smoking in the postpartum period [5].…”
Section: Introductionmentioning
confidence: 99%